Antiviral therapy of symptomatic HCV‐associated mixed cryoglobulinemia: Meta‐analysis of clinical studies. Issue 6 (12th April 2013) - Fabrizi, Fabrizio; Dixit, Vivek; Messa, Piergiorgio
Abstract: Hepatitis C virus (HCV) infection may be associated with extra‐hepatic illness including mixed cryoglobulinemia. Evidence on HCV‐related mixed cryoglobulinemia in the non‐transplantation setting exists even if its appropriate management remains unclear. The cornerstone of treatment for symptomatic HCV‐associated mixed cryoglobulinemia is antiviral therapy but little is known about its activity. A systematic review of the literature with a meta‐analysis of clinical studies was performed in order to assess efficacy and safety of combination antiviral therapy for symptomatic HCV‐associated mixed cryoglobulinemia in non‐immunosuppressed individuals. The random effects model of DerSimonian and Laird was used, with heterogeneity and sensitivity analyses. The primary outcome was sustained virological response (as a measure of efficacy), and the secondary outcome was the rate of patients stopping (or dose reducing) antiviral agents (as a measure of tolerability). Ten clinical studies (300 unique patients) were identified; the rate of baseline kidney involvement ranged between 4% and 39%. The summary estimate of frequency of sustained viral response was 0.42 with a 95% confidence interval (CI) of 0.31; 0.54 (random effects model). Significant heterogeneity occurred ( P  = 0.00001; I 2  = 77.6%). Stratified analysis showed higher efficacy in those studies using combination therapy with pegylated—than conventional IFN; the summary estimate of sustained viral response being 0.52 (95% CI, 0.40; 0.63) and 0.32 (95% CI, 0.15; 0.49), respectively. There was good association between viral and clinical response, weighted K 0.634 (95% CI, 0.455; 0.814), by a meta‐analysis at individual level on a subset of reports (n = 3; 74 unique patients). The summary estimate of frequency of patients stopping (or dose reducing) antiviral agents was 0.15 (95% CI, 0.08; 0.21); no heterogeneity occurred ( P  = 0.05; I 2  = 51%). In summary, combination antiviral therapy (pegylated IFN plus ribavirin) gives satisfactory response in more than the half of patients with symptomatic mixed cryoglobulinemia associated with HCV. HCV‐related mixed cryoglobulinemia is uncommon in developed countries and this clearly hampers randomized controlled clinical trials aimed to evaluate efficacy and safety of antiviral therapy in non‐immunosuppressed individuals. J. Med. Virol. 85: 1019–1027, 2013. © 2013 Wiley Periodicals, Inc.